SPECIALIZED MAPS AND REGISTERS – GENERAL APPROACHES TO THEIR CREATION: SPECIALIZED MAPS AND REGISTERS – GENERAL APPROACHES TO THEIR CREATION - Niyazi-Yusuf, Mirem (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The article examines the main principles and approaches in the creation of specialized maps and registers. It highlights their role as tools for spatial analysis, planning, and management. The main stages of work are presented – from data collection and standardization to visualization and maintenance. Emphasis is placed on a systematic and standardized approach that ensures the accuracy, reliability, and interoperability of the data.